La creación de un modelo de análisis de la información visual, sonora y háptica en un videojuego para la mejora de accesibilidad a personas con discapacidad visual - Martínez Barahona, Jaime; García García, Francisco; Estupiñán, Óscar (CEM – Cultura, Espaço & Memória, 2020)
People with visual impairment are one of the groups with more difficulties to enjoy the audiovisual products, even more in the case of video games. Universal accessibility tries to take down those barriers and to reach that goal it needs to find alternative procedures to the visual channel in order to communicate the same information and interaction. A model to analyze the information communicated in their different levels and screens, through the visual, sound and haptic channels, will help to identify the information that is just communicated through pictures, with subsequent possible applications to the accessibility of that game.